Emanuel Edward Klein, a diligent and industrious plodder or the father of British microbiology - Bruno Atalić; Ines Drenjančević-Perić; Stella Fatovic-Ferenčić (Medicinski Glasnik, 2010)
Emanuel Edward Klein (Osijek, 1844 - Hove, 1925) was a Britishmicrobiologist of Croatian origin. He completed his medical studies in Vienna in 1869. In 1869 he was sent to England to determine terms for the translation of Samuel Stricker’s manual Handbuch von den Geweben des Menchen und der Tiere. During his visit he made a good impression on John Burdon Sanderson and John Simon, which was the main reason why he was invited to London in 1871 to conduct investigations under their guidance. In 1873 Klein began his collaboration with the Saint Bartholomew‘s Hospital, where he was appointed as a Joint Professor of General Anatomy and Physiology. His researches were in the fields of anatomy, histology, pathology, embryology, physiology, and especially microbiology. He did a great deal to its development in Britain. He has written about 260 scientific papers on a broad range of different topics. Despite all the aforementioned facts, his work was never properly studied, and he is almost unknown outside academic circles. For that reason, attitudes towards him still range between the extremes of calling him the father of British microbiology on one side, and attributing him as a diligent and idustrious plodder on the other. In this paper we will try to prove the first attitude. We will put his researches in a general context. Finally we will highlight his original achievements in the isolation of new microbes.